Macrolide resistance mechanisms in Enterobacteriaceae: Focus on azithromycin - Gomes, C (2017)
From its introduction in 1952 onwards, the clinical use of macrolides has been steadily increasing, both in human and veterinary medicine. Although initially designed to the treatment of Gram-positive microorganisms, this antimicrobial family has also been used to treat specific Gram-negative bacteria. Some of them, as azithromycin, are considered in the armamentarium against Enterobacteriaceae infections. However, the facility that this bacterial genus has to gain or develop mechanisms of antibiotic resistance may compromise the future usefulness of these antibiotics to fight against Enterobacteriaceae infections. The present review is focused on the mechanisms of macrolide resistance, currently described in Enterobacteriaceae.